Training program influences the relation between functional and neuromuscular performance indicators during the season in young soccer players - Spigolon,Leandro Mateus Pagoto (2017)
Abstract The aim of this study was to investigate the influence of a training program on the relation between performance indicators of different physical capacities intra and inter functional and neuromuscular systems at different times of the season. Subjects were 16 young soccer players with an average age of 16.5 ± 0.4 years. The study was carried out for 17 weeks, including three assessment moments (T1: 1st, T2: 10th and T3: 17th week). High correlation was found between indicators of neuromuscular predominance (30 meters sprint test (30 m) and Maximum Sprint (MaxSprint) (RAST) in T1) (r = 0.93, p ≤ 0.001), functional (Sprints Average (MidSprint) and Minimal Sprint (MinSprint) (RAST) in T1, T2 and T3; MinSprint and Fatigue Index (FI) (RAST) in T3) (r = 0.95, 0.85, 0.91; -0.86, p ≤ 0.001, respectively) and between functional and neuromuscular indicators (30 m and MidSprint in T1; 30 m and MinSprint in T1; MaxSprint and MidSprint in T1 and T2 and MaxSprint and MinSprint in T1) (r = 0.95, 0.93, 0.96, 0.84, 0.87, p ≤ 0.001, respectively). The training contents had influence on the correlation of performance indicators at different times of the season.